Empirical analysis to the factors impact on succession process of the family-owned businesses in Bangladesh, moderating role of education - Hossain, Md. Shahadat; Islam, Md. Asadul; Haque, A. K. M. Ahasanul (Inderscience Publishers, 2022)
The purpose of this study is to examine the impact of the factors such as governance board, gender and business strategies on the succession planning in family-owned businesses (FOBs) in Bangladesh. Moreover, the study also examines the moderating role of education on the relationship between the governance board, gender and business strategies on the succession planning in FOBs in Bangladesh. Data obtained from 287 participants were analysed using PLS-SEM to test the hypotheses. The results show that the governance board has a significant impact on the succession process in FOBs in Bangladesh. However, this study finds no impact of gender and business strategies on the succession process in the family-owned businesses in Bangladesh. Moreover, education plays a moderating role only on the relationship between the governance board and succession process in FOBs. Implications of the findings including research limitations and future directions have been discussed.